MEMS Seismic Sensor with FPAA Based Interface Circuit for Frequency-Drift Compensation using ANN - Ramesh Pawase; N.P. Futane (Institute of Advanced Engineering and Science, 2017)
Electrochemical MEMS seismic sensor is limited by its non-ideality of frequency dependent characteristics hence interface circuits for compensation is necessary. The conventional compensation circuits are limited by high power consumption, bulky external hardware circuitry. In these methods digital circuits are also limited by inherent analog to digital conversion and vice versa which consumes significant power, acquires more size and limits speed. A Field programmable analog array (FPAA) overcomes these limitations and gives fast, simple and user friendly development platform with less development speed comparable to ASIC. Recently FPAA becoming popular for rapid prototyping. The proposed system presents FPAA (Anadigm AN231E04) based hardware implementation of ANN model. Using this FPAA based compensation circuit, the error in frequency drift have been minimized in the range of 3.68% to about 0.64% as compared to ANN simulated results in the range of 23.07% to 0.99 %. This single neuron consumes of power of 206.62 mW. and has minimum block wise resource utilization. The proposed hardware uses all analog blocks which remove the requirement of ADC and DAC reducing significant power and size of interface circuit. This work gives the SMART MEMS seismic sensor with reliable output and ANN based intelligent interface circuit implemented in FPAA hardware.